Inflammatory changes in the choroid plexus following subarachnoid hemorrhage: the role of innate immune receptors and inflammatory molecules - Solár, Peter; Brázda, Václav; Bareš, Martin; Zamani, Alemeh; EmamiAref, Parisa; Joukal, Andrea; Kubíčková, Lucie; Kročka, Erik; Hašanová, Klaudia; Joukal, Marek (Frontiers in Cellular Neuroscience, 2025)
IntroductionThe choroid plexus is located in the cerebral ventricles. It consists of a stromal core and a single layer of cuboidal epithelial cells that forms the blood-cerebrospinal barrier. The main function of the choroid plexus is to produce cerebrospinal fluid. Subarachnoid hemorrhage due to aneurysm rupture is a devastating type of hemorrhagic stroke. Following subarachnoid hemorrhage, blood and the blood degradation products that disperse into the cerebrospinal fluid come in direct contact with choroid plexus epithelial cells. The aim of the current study was to elucidate the pathophysiological cascades responsible for the inflammatory reaction that is seen in the choroid plexus following subarachnoid hemorrhage.MethodsSubarachnoid hemorrhage was induced in rats by injecting non-heparinized autologous blood to the cisterna magna. Increased intracranial pressure following subarachnoid hemorrhage was modeled by using artificial cerebrospinal fluid instead of blood. Subarachnoid hemorrhage and artificial cerebrospinal fluid animals were left to survive for 1, 3, 7 and 14 days. Immunohistochemical staining of TLR4, TLR9, FPR2, CCL2, TNFα, IL-1β, CCR2 and CX3CR1 was performed on the cryostat sections of choroid plexus tissue. The level of TLR4, TLR9, FPR2, CCL2, TNFα, IL-1β was detected by measuring immunofluorescence intensity in randomly selected epithelial cells. The number of CCR2 and CX3CR1 positive cells per choroid plexus area was manually counted. Immunohistochemical changes were confirmed by Western blot analyses.ResultsImmunohistochemical methods and Western blot showed increased levels of TLR9 and a slight increase in TLR4 and FRP2 following both subarachnoid hemorrhage as well as the application of artificial cerebrospinal fluid over time, although the individual periods were different. The levels of TNFα and IL-1β increased, while CCL2 level decreased slightly. Accumulation of macrophages positive for CCR2 and CX3CR1 was found in all periods after subarachnoid hemorrhage as well as after the application of artificial cerebrospinal fluid.DiscussionOur results suggest that the inflammation develops in the choroid plexus and blood-cerebrospinal fluid barrier in response to blood components as well as acutely increased intracranial pressure following subarachnoid hemorrhage. These pro-inflammatory changes include accumulation in the choroid plexus of pro-inflammatory cytokines, innate immune receptors, and monocyte-derived macrophages.